Glutamate dehydrogenases in the oleaginous yeast Yarrowia lipolytica. Issue 1 (8th August 2019) - Trotter, Pamela J.; Juco, Karen; Le, Ha T.; Nelson, Kjersten; Tamayo, Lizeth I.; Nicaud, Jean‐Marc; Park, Young‐Kyoung
Abstract: Glutamate dehydrogenases (GDHs) are fundamental to cellular nitrogen and energy balance. Yet little is known about these enzymes in the oleaginous yeast Yarrowia lipolytica . The YALI0F17820g and YALI0E09603g genes, encoding potential GDH enzymes in this organism, were examined. Heterologous expression in gdh ‐null Saccharomyces cerevisiae and examination of Y. lipolytica strains carrying gene deletions demonstrate that YALI0F17820g ( ylGDH1 ) encodes a NADP‐dependent GDH whereas YALI0E09603g ( ylGDH2 ) encodes a NAD‐dependent GDH enzyme. The activity encoded by these two genes accounts for all measurable GDH activity in Y. lipolytica . Levels of the two enzyme activities are comparable during logarithmic growth on rich medium, but the NADP‐ylGDH1p enzyme activity is most highly expressed in stationary and nitrogen starved cells by threefold to 12‐fold. Replacement of ammonia with glutamate causes a decrease in NADP‐ylGdh1p activity, whereas NAD‐ylGdh2p activity is increased. When glutamate is both carbon and nitrogen sources, the activity of NAD‐ylGDH2p becomes dominant up to 18‐fold compared with that of NADP‐ylGDH1p. Gene deletion followed by growth on different carbon and nitrogen sources shows that NADP‐ylGdh1p is required for efficient nitrogen assimilation whereas NAD‐ylGdh2p plays a role in nitrogen and carbon utilization from glutamate. Overexpression experiments demonstrate that ylGDH1 and ylGDH2 are not interchangeable. These studies provide a vital basis for future consideration of how these enzymes function to facilitate energy and nitrogen homeostasis in Y. lipolytica .